2020
DOI: 10.17728/jatp.5480
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisasi Plantarisin IIA-1A5 sebagai Antimikroba dan Evaluasi Aktivitas Sediaan Kering Beku Terenkapsulasi

Abstract: Bakteriosin adalah peptida dengan aktivitas antibakteri yang diproduksi oleh bakteri asam laktat dan digunakan sebagai pengawet alami. Penelitian sebelumnya menunjukkan bahwa Lactobacillus plantarum IIA-1A5 memproduksi bakteriosin yang diberi nama Plantarisin IIA-1A5 pada medium pertumbuhan yang dibuat dari whey yang diperkaya skim. Untuk aplikasi sebagai pengawet alami dan untuk memperbaiki masa simpan dan aktivitas anti mikrobanya, plantarisin perlu dienkapsulasi dan dikeringbekukan. Tujuan dari penelitian i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Gram positive bacteria were more sensitive, while gram negative bacteria were more resistant (Fatmarani et al 2018). Based on the research results of Soenarno et al (2020), that plantaricin IIA-1A5 has a broad spectrum antimicrobial ability against Gram positive and Gram negative pathogenic bacteria.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Gram positive bacteria were more sensitive, while gram negative bacteria were more resistant (Fatmarani et al 2018). Based on the research results of Soenarno et al (2020), that plantaricin IIA-1A5 has a broad spectrum antimicrobial ability against Gram positive and Gram negative pathogenic bacteria.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Arief et al (2015) reported that the molecular weight of crude plantaricin IIA-1A5 was less than 10 kDa and was classified in the IIA classification. The plantaricin IIA-1A5 was successfully purified using cation exchange chromatography, and had a molecular weight of 9.65 kDa (Soenarno et al 2020). This is similar to the study of Arifin et al (2020), that plantaricin IIA-1A5 was successfully purified from ammonium sulfate, and cation exchange chromatography and had a molecular weight of 9.4 kDa.…”
Section: Characteristics Of Crude Plantaricin Iia-1a5mentioning
confidence: 99%
See 2 more Smart Citations